Effects of sex, eye-side, diurnal variation on intraocular pressure in calves - Kulualp, K.; Kilic, S.; Aytekin, O. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2019)
The aim of this study was to determine the effects of factors such as sex, eye-side and diurnal variation on intraocular pressure (IOP) values measured by Tono-Pen Vet (R) in healthy calves. Twenty four (12 males, 12 females) calves were used in this study. IOP measurements were performed in the morning (6: 00 a.m.) and at night (8: 00 p.m). Average IOP values in all calves were measured as 17.67 +/- 2.64 mmHg in the morning and 15.52 +/- 2.05 at night and the difference between these two time points was found to be statistically significant (p<0.0001). Average IOP values were measured as 16.04 +/- 2.82 mmHg in males and 17.15 +/- 2.23 mmHg in females with a statistically significant (p<0.05=0.023) difference between them. Average IOP values were 16.81 +/- 2.85 mmHg in right eyes and 16.37 +/- 2.23 mmHg in left eyes and the difference between these values were statistically insignificant (p>0.05). At the end of study, overall average IOP in all calves was measured as 16.59 +/- 2.59 mmHg. The present data showed a significant difference in terms of sex and diurnal variations and a non-significant difference in eye-side. In addition, this study is the first research article in which the intraocular pressure in calves was measured by Tono-Pen Vet
Keywords: calves; intraocular pressure; Tono-Pen Vet (R); sex; eye-side; diurnal variation